INPUT SUPPLY CATFISH (Pangasius hypopthalmus) FILLET PRODUCTS PUBLIC CORPORATION ( PERUM ) INDONESIAN FISHERY IN PROCESSING UNITS FISH (UPI) DISTRICT MUARO JAMBI JAMBI PROVINCE - Rabbil Muhammad; Eni Yulinda; Hendrik ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted in May 2016 located in Jambi processing units fish (UPI) subsdistrict Taman Rajo district Muaro Jambi, Jambi province. Research aims to knew about input products, investment and profit processing catfish fillet in unit fish processing Muaro Jambi. Methods used in research was case study with the number of respondents was 15 people. The raw material for making catfish with average about 10.000 kg (10 tons) per month produce fillet about 5 tons, raw materials derived from fish farmer in 7 village from district Muaro Jambi. Number of workers as many as 15 passenger with details 2 workers fixed and 13 workers no fixed. Investment management catfish fillet in Muaro Jambi Rp 1.170.975.000,- meanwhile total cost (fixed costs and variable costs) issued Rp 174.519.931,- per month. Gross income received in once production by Rp 243.309.000,- per month and net income of Rp 68.789.069,- per month.Keywords: input supply, fillet, investments, UPI, Muaro Jambi